(untitled) (PerCursos, 2023)
This article proposes to discuss the psychosocial impact of the COVID-19 pandemic on the triple border (Argentina/Brazil/Paraguay), with a special focus on the black population. Considering the analytical potential existing in the condition of life in a border region, in this article, we face the processes around mental health and psychic suffering and their unfolding in cross-border health discourses and practices. The essay intends to answer the question of how racism is expressed in mental health, and it does so in two movements; Initially, it problematizes the health indicators of the black population in the context of the pandemic and, at the same time, reinforces that a significant part of the health indicators are worked without the cut of race/color and this is not by mere chance, it is part of the necropolitical strategy (Mbembe, 2018) to make historical, social and political plots of racism invisible. From this point on, the aspects related to psychic suffering and mental health during the pandemic are discussed to demonstrate how the quarantine strategy adopted at the triple border was to take care of bourgeois whiteness. The point of arrival is a reflection on mental health linked to a conception not limited to psi knowledge, that is, psychology, psychoanalysis, and psychiatry, knowledge that is hegemonic in the understanding that we have historically built around mental health. But, on the other hand, it presents itself with a conception of mental health that starts from the totality, the contradictions, and the historicity of the people who live in this border region.